Moderasi Beragama pada Gereja Masehi Injili di Halmahera (GMIH), Wilayah Pelayanan Tobelo - Tiang, Desyane Silce; Nanuru, Ricardo Freedom; Petrus, Jerizal (KURIOS, 2023)
This research aims to determine the extent to which religious moderation programmed by the Ministry of Religion of the Republic of Indonesia since 2019 has a place in the life of the Evangelical Christian Church in Halmahera (GMIH) Tobelo Service Area. This research uses qualitative research methods, which emphasize phenomena and examine the substance of the meaning of these phenomena. This research found that ideally, religion should not be a source of conflict but rather a guide for society to live a pluralistic life; strengthening religious moderation is vital to building national culture and character; in the Indonesian context, moderate religion can be used as a cultural strategy to maintain an Indonesia that is peaceful, tolerant, and respects religion; the religious moderation program has not been well received and implemented by the church as a government partner, less popular among local churches like the Evangelical Christian Church in Halmahera (GMIH).Â In conclusion, local churches, such as GMIH, play an essential role in building religious moderation, cultivating it in a structured manner within its internal circles through work programs regulated from the synodal level to the congregations.AbstrakPenelitian ini bertujuan untuk menemukan sejauh mana moderasi beragama yang diprogramkan oleh Kementerian Agama Republik Indonesia sejak tahun 2019 mendapat tempat dalam kehidupan Gereja Masehi Injili di Halmahera (GMIH), Wilayah Pelayanan Tobelo. Penelitian ini menggunakan metode penelitian kualitatif, yang menekankan pada fenomena dan lebih meneliti ke substansi makna dari fenomena tersebut. Penelitian ini menemukan bahwa, idealnya agama tidak menjadi sumber konflik, melainkan menjadi pedoman bagi masyarakat tentang bagaimana hidup di tengah keberagaman; penguatan moderasi beragama menjadi penting sebagai upaya membangun kebudayaan dan karakter bangsa; dalam konteks ke-Indonesia-an, moderasi beragama dapat dijadikan sebagai strategi kebudayaan untuk merawat Indonesia yang damai, toleran, dan menghargai keragamaan; dan, program moderasi beragama belum secara baik diterima dan dilakukan oleh gereja sebagai mitra pemerintah, kurang bergaung di kalangan Gereja Masehi Injili di Halmahera (GMIH). Kesimpulannya,Â gereja lokal, seperti GMIH, memegang peranan penting dalam membangun moderasi beragama, membudayakannya secara terstruktur di kalangan internalnya, melalui program kerja yang diatur dari tingkat sinodal sampai ke jemaat-jemaat.